Towards a Better Measure of Customer Experience - Klaus, P; Maklan, Stan (Cranfield University, 2013)
Defining and improving customer experience is a growing priority for market research because experience is replacing quality as the competitive battleground for marketing. Service quality, we argue, is an outgrowth of the Total Quality Management movement of the 1980s and suffers from that movement’s focus on the provider rather than the value derived by customers. The most popular measure of service quality – SERVQUAL – assesses the functional delivery of service during a single episode. This conceptualisation allows service to be improved along traditional quality management principles. The increasingly settled view of researchers is that customer experience is generated through a longer process of company-customer interaction across multiple channels and is generated through both functional and emotional clues. Research with practitioners indicates that most firms use customer satisfaction, or its derivative Net Promoter Score, to assess their customers’ experiences. We question this practice based on the conceptual gap between these measures and the customer experience. In the IJMR October 2011, we proposed the principles of a new measure appropriate for the modern conceptualisation of customer experience: the Customer Experience Quality (EXQ) scale. In this article we extend that work to four service contexts to support a claim of generalisability better and compare its predictive power with that of customer satisfaction. We propose that EXQ better explains behavioural intention and recommendation than customer satisfaction.